Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di MIS Baja Kuning - Azmar Azmar; Makmur Syukri; Rija Ansari; Abdul Latif Hutagaol; Elfin Nazri (Departement of Mathematics Education, 2023)
This research uses qualitative methods with the aim of looking at the phenomena that exist in the school related to the leadership of the principal in improving the quality of education at MIS Baja Kuning. The results of the research show that quality education basically produces quality human resources as well. The quality of education is determined by various elements, namely school, community, and family involvement. In making quality schools, it is necessary to have a quality policy in schools. The quality policy in schools is an official and written policy from a school where the school community is committed to realizing this policy. In making decisions and policies on the quality of education at MIS Baja Kuning, the Principal together with the teachers develops and improves the quality of the school by carrying out deliberations to formulate the vision, mission and goals of the school to be achieved. Then a better policy is carried out that serves as a guideline for long-term school policy directions in terms of continuous quality improvement. That way in making decisions and policies at MIS Baja Kuning has a process in improving the quality of education in order to achieve the goals of school education as expected.